A Construct Validation Study of the Career Well-Being Scale for Vocational School Students using Confirmatory Factor Analysis - Muhammad Rafli; Muzayyinah Al Usrah; Dewi Pratiwi; Agus Qomaruzzaman (Research in Education, Technology, and Multiculture, 2024)
Abstract: This study focuses on the concept and measurement of career well-being as part of the early detection for career planning preparation among vocational high school (VHS) students. The aim is to assist students in fostering optimal career development, ultimately reducing the risk of anxiety and stress that could interfere with their future careers. This research employs a quantitative scale study, with a measurement tool that has been adapted and translated into Indonesian. The respondents in this study (N = 201) are students of Vocational High School 1 Bantaeng, who are currently enrolled in their educational program. Data collection was conducted using the Career Well-Being Scale (CWS), developed by Coetzee et al. (2021), which aims to assess career well-being in career choice, consisting of 14 items across three dimensions. The data analysis employed descriptive statistics and Confirmatory Factor Analysis (CFA), conducted using the JASP statistical software. Based on the results, the Career Well-Being Scale demonstrated excellent consistency in measuring the construct among VHS students. This instrument has proven to be reliable for providing stable and valid measurements, with items that mutually support each other in depicting the dimensions of career well-being.     Keywords: development of the scale, career well-being; scale validation, students.